2021
DOI: 10.3233/jad-201364
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Risk Models for Persons with Dementia: A Systematic Review

Abstract: Background: Persons with dementia have higher mortality than the general population. Objective, standardized predictions of mortality risk in persons with dementia could help with planning resources for care close to the end of life. Objective: To systematically review prediction models for risk of death in persons with dementia. Methods: The Medline and PsycInfo databases were searched on November 29, 2020, for prediction models estimating the risk of death in persons with dementia. Study quality was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 28 publications
1
24
1
Order By: Relevance
“…A recent systematic review suggested that ADEPT is a reliable prognostic tool for predicting risk of death at 6 months among persons with advanced dementia in nursing homes [30]. However, our EOL diagnostic method had a higher DOR (10.32, 95% CI 4.08-26.13) than ADEPT score ≥ 18 (2.58, 95% CI 1.05-6.37) in our study populations (Table 4).…”
Section: Discussionmentioning
confidence: 59%
“…A recent systematic review suggested that ADEPT is a reliable prognostic tool for predicting risk of death at 6 months among persons with advanced dementia in nursing homes [30]. However, our EOL diagnostic method had a higher DOR (10.32, 95% CI 4.08-26.13) than ADEPT score ≥ 18 (2.58, 95% CI 1.05-6.37) in our study populations (Table 4).…”
Section: Discussionmentioning
confidence: 59%
“…A follow-up analysis suggested that cognitive scores predicted attrition in the current sample. This could have led to an underestimation of the true rates of cognitive decline, biasing results toward the null hypothesis, as both sensory and cognitive challenges are negatively associated with survival (Ehrlich et al, 2021; Smith & Ismail, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…8 However, like the FAST Stage 7c (nonambulatory), the ADEPT score alone is not very suitable for forecasting death. 9 The ADEPT tool was found to be 68% accurate in predicting death over 6 months, while the FAST scale was 55% accurate in patients living in LTC facilities. 8 Since these tools are limited, nurses must consider a patient' s goals of care as the overarching guide when making endof-life decisions with their families and surrogates.…”
Section: Middle Stage: the Signs And Symptoms Become Clearer And May ...mentioning
confidence: 91%
“…A recent systematic review of dementia prognostic models indicated that the best validated prognostic model for advanced dementia is the 12-item Advanced Dementia Prognostic Tool (ADEPT). 9 Another study found ADEPT to be marginally better than the Medicare Hospice Guidelines and have moderate accuracy to predict 6-month survival in patients with advanced dementia. 8 However, like the FAST Stage 7c (nonambulatory), the ADEPT score alone is not very suitable for forecasting death.…”
Section: Middle Stage: the Signs And Symptoms Become Clearer And May ...mentioning
confidence: 99%